2002
DOI: 10.1006/redy.2001.0149
|View full text |Cite
|
Sign up to set email alerts
|

The 1990s in Japan: A Lost Decade

Abstract: This paper examines the Japanese economy in the 1990s, a decade of economic stagnation. We find that the problem is not a breakdown of the financial system, as corporations large and small were able to find financing for investments. There is no evidence of profitabkle investment opportunities not being exploited due to lack of access to capital markets. The problem then and still today is a low productivity growth rate. Growth theory, treating TFP as exogenous, accounts well for the Japanese lost decade of gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
351
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 627 publications
(382 citation statements)
references
References 8 publications
14
351
1
4
Order By: Relevance
“…Second, we analysed the rate of return on capitals using models that deal with simultaneity bias, and found that our results contradict those in previous studies. Furthermore, this paper is novel in that it applies 18 The result is consistent with that by Hayashi and Prescott (2002). Jorgenson and Nomura (2007) also demonstrate that the TFP growth of the Japanese manufacturing sector stalled during between 1990 and 2000, which is consistent with our findings in this paper.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Second, we analysed the rate of return on capitals using models that deal with simultaneity bias, and found that our results contradict those in previous studies. Furthermore, this paper is novel in that it applies 18 The result is consistent with that by Hayashi and Prescott (2002). Jorgenson and Nomura (2007) also demonstrate that the TFP growth of the Japanese manufacturing sector stalled during between 1990 and 2000, which is consistent with our findings in this paper.…”
Section: Discussionsupporting
confidence: 87%
“…However, the number of patent applications by Japanese firms in the United States is little more than 20%. 5 Low TFP growth was a key reason for the Japanese lost decade (Hayashi, Prescott 2002;Jorgenson, Nomura 2007). Branstetter and Nakamura (2003) show that R&D productivity of Japanese firms reached a plateau around 1990 and grew little thereafter.…”
Section: Previous Studiesmentioning
confidence: 99%
“…According to Hayashi and Prescott (2002) the persistent low productivity growth since the Lost Decades is driven by a weak TFP expansion, compared to the earlier period. It might be linked to low incentives of firms to innovate in highly protected markets (Hamao, Mei and Xu, 2007).…”
Section: Growth Trends In Japan and The Euro Areamentioning
confidence: 99%
“…The TFP (total factor productivity) growth calculated by the macro growth accounting, therefore, confuses genuine TFP growth with the contribution of IT capital to the growth of capital services. Hayashi and Prescott (2002) showed that Japan's great stagnation in the 1990s is wellaccounted for by the standard neoclassical growth model with a TFP slowdown in the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…It distinguishes between non-IT capital and IT capital in the production function. In Section 5, following Hayashi and Prescott (2002), we calibrate the model to the Japanese economy in the 1984-89 period and report results from the simulation of the model from year 1990 on. The multi-sector model does well in accounting for the output slump of the 90s but less well than the one-sector model for the rise in the capital-output ratio in the 1990s.…”
Section: Introductionmentioning
confidence: 99%